Study protocol for a systematic review with meta-analysis to compare digital stress tests regarding their psychological and physiological stress responses - Reiser, Lara; Diaconescu, Luciana; Rohleder, Nicolas (PLoS ONE, 2025)
BACKGROUND AND AIM: Stress is a phenomenon of everyday life that all humans are exposed to, and that can have negative effects on health. Exposure to chronic stress has been associated with development of several diseases, but also acute stress can have detrimental health effects. To understand acute stress, standardized laboratory protocols are frequently employed. However, these protocols require considerable personal and financial resources, and are therefore usually uneconomical. More and more digitized, automated protocols are currently being developed, which may enable a more cost-effective and less time-consuming implementation, but these have not been systematically examined and compared. The aim of the proposed systematic review is therefore to provide a comprehensive overview of different digital stress tests and to compare them in terms of the elicited stress responses. METHODS: This study protocol was registered with PROSPERO, and PRISMA-P guidelines were followed. We will screen several online databases for eligible studies in English or German without any restrictions on the publication date using an a priori defined search strategy. Additionally, we will search those papers for other eligible studies. The primary outcome will be stress and/or similar psychological states. The search, selection and data extraction processes will be conducted by two independent reviewers. In case of discrepancy a third reviewer will be consulted. If possible, we will perform meta-analyses. To determine confidence in results we will assess risk of bias and overall quality of evidence. Additionally, results will be critically examined to avoid meta-biases. DISCUSSION: To the best of our knowledge, no systematic reviews or meta-analyses are published comparing digital stress tests - designed to elicit stress and/or similar psychological states. In this study protocol, we propose a systematic review analyzing existing digital stress tests, and examining their effectiveness by measuring acute stress responses.
CRIS-Team Scopus Importer:2025-10-10